(untitled) (Journal of Atomic and Molecular Sciences, 2013)
A detailed quantum chemical study is performed on the mechanism of the CH_3OCHFO radical formed during the photooxidation of CH_3OCH_2F (HFE-161), including the main decomposition and isomerization processes at the G2(MP2)//MPWB1K level of theory. The results clearly point out that the β-C-H bond scission is the dominant path involving the lowest energy barrier of 8.16 kcal mol^-1 calculated at G2(MP2) level of theory. On the basis of the results obtained during the present investigation, the thermal rate constant for the different reaction channels involved during the isomerization and decomposition processes of CH_3OCHFO are evaluated at 298 K and 1 atm using Canonical Transition State Theory. The results are compared with the data available in the literature.